PEMANFAATAN HANDPHONE DI KALANGAN MAHASISWA - Gusti Yarmi, Ika Lestari (Perspektif Ilmu Pendidikan, 2017)
This study aims to identify the utilization of application programs on mobile phones in the student learning process. This research is a requirement analysis step from development research entitled â€œDevelopment of Moodle Based Learning Mobile for Learning in Higher Educationâ€. The study was conducted from March to May 2017 involving 64 students for the course of Development of Learners. This research was used survey research method with quantitative approach. The data was collected by an open questionnaire given to 64 students. Data analysis technique used is descriptive statistical analysis. The result of the research shows that there is still minimal use of mobile phones to be used in learning process and student learning and there are still many social media applications that are often opened by students. This research has implications for the presence of a moodle-based mobile learning application that can be used by students to study in the classroom.